2008
DOI: 10.1111/j.1440-1797.2008.00999.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated circulating levels of soluble CD‐40 ligand in haemodialysis patients with symptomatic coronary heart disease

Abstract: Circulating concentrations of sCD40L were elevated in HD patients with symptomatic CHD. This study suggests that CD40-CD40L may play a potentially important role in the atherosclerotic complications of HD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…It is mostly generated by activated platelets and elevated in stage-5 CKD patients with CVD. 40 Consistent with our findings, sCD40L levels were found to be elevated in HHcy patients and positively correlated with Hcy. 36 Our study is the first to connect CD40L elevation with MC differentiation and to validate this connection in experimental models.…”
Section: Discussionsupporting
confidence: 92%
“…It is mostly generated by activated platelets and elevated in stage-5 CKD patients with CVD. 40 Consistent with our findings, sCD40L levels were found to be elevated in HHcy patients and positively correlated with Hcy. 36 Our study is the first to connect CD40L elevation with MC differentiation and to validate this connection in experimental models.…”
Section: Discussionsupporting
confidence: 92%
“…sCD40L ligand concentrations are associated with an increased risk of cardiovascular events in the general population 56 and are increased in patients with MHD. 57 We found that sCD40L increased during dialysis and there was no difference among the treatment arms. Koh et al also reported that 2 months of treatment with candesartan reduced the plasma levels of sCD40L in hypertensive patients.…”
Section: Discussionmentioning
confidence: 64%
“…Protein carbonylation plays an important role in the etiology and/or progression of several human diseases such as cardiovascular and neurodegenerative diseases [39]. PC was significantly elevated in patients with symptomatic coronary heart disease (CHD) in end-stage renal disease on maintenance hemodialysis (HD) compared to those without [40]. In the present study, LS and HS supplementation markedly increased PC over no supplementation regardless of MeHg treatment and these increases in PC were not associated with increases in other serum markers except ICAM-1 examined.…”
Section: Discussionmentioning
confidence: 99%